Predictive Value of Volumetric Measurements of Fetal Adrenal Glands for Preterm Birth: A Case-Control Study - Alper Basbug; Engin Yurtcu; Betul Keyif; Askı Ellibes Kaya; Mehmet Ali Sungur; Fikret Gokhan Goynumer; Safak Hatırnaz; Radmila Sparic; Andrea Tinelli; Michael H. Dahan (Clinical and Experimental Obstetrics & Gynecology)
Background: To investigate whether fetal adrenal gland volume (AGV) and fetal zone volume (FZV), important components of the fetal adrenal gland, differ between women who have term and preterm births, and to determine whether these two parameters can be used to predict premature birth. Methods: A total of 238 pregnant women at 24–28 weeks of gestation were included in this case-control study. The fetal AGV and FZV were ultrasonographically evaluated, and corrected AGV (cAGV) and corrected FZV (cFZV) were assessed with adjustments for estimated birth weight. Receiver operating characteristic (ROC) curves were used to assess the ability of AGV, FZV, cAGV, and cFZV to predict preterm birth. Results: Ultrasound exams on 220 term fetuses and 18 preterm fetuses showed that preterm fetuses exhibited higher AGV (p = 0.039), FZV (p = 0.001), cAGV (p = 0.001), and cFVZ (p = 0.001) compared to term fetuses. Conclusions: These results demonstrated that term and preterm fetuses differ in their AGV and FZV within this study population. The data generated by 3D sonography between 24 and 28 weeks of gestation may be beneficial for predicting premature birth. However, larger prospective studies with a larger sample size of preterm births are needed to validate these findings.